Compilation of a standardised international folate database for EPIC. (15th February 2016) - Nicolas, Geneviève; Witthöft, Cornelia M.; Vignat, Jérôme; Knaze, Viktoria; Huybrechts, Inge; Roe, Mark; Finglas, Paul; Slimani, Nadia
Highlights: This work can serve as reference for international database compilation. Microbiological assay was chosen as the reference analytical method. Many values in food composition tables were not documented regarding their origin. Precise documentation of published values is essential to assess data quality. This database provides more accurate and comparable folate values across countries. Abstract: This paper describes the methodology applied for compiling an "international end-user" folate database. This work benefits from the unique dataset offered by the European Prospective Investigation into Cancer and Nutrition (EPIC) ( N  = 520, 000 subjects in 23 centres). Compilation was done in four steps: (1) identify folate-free foods then find folate values for (2) folate-rich foods common across EPIC countries, (3) the remaining "common" foods, and (4) "country-specific" foods. Compiled folate values were concurrently standardised in terms of unit, mode of expression and chemical analysis, using information in national food composition tables (FCT). 43–70% total folate values were documented as measured by microbiological assay. Foods reported in EPIC were either matched directly to FCT foods, treated as recipes or weighted averages. This work has produced the first standardised folate dataset in Europe, which was used to calculate folate intakes in EPIC; a prerequisite to study the relation between folate intake and diseases.